Promoting Children’s Welfare in the Nordic Countries - Hiilamo, Heikki (sosiaali- ja terveysministeriö, 2008)
The aim of this study is to describe and compare the institutions that promote the welfare of children and youth in Nordic countries. These institutions concern policies that are related to child welfare in five Nordic countries, namely Denmark, Finland, Norway, Iceland and Sweden. The decision to exclude autonomous territories, Faroe Islands (Denmark), Greenland (Denmark) and Åland (Finland), was based on the fact that most programmes promoting child welfare in these territories do not have distinctive features. By institutions promoting the welfare of children and youth we mean the overall system in each country under which public authorities, private actors and third sector parties (NGO’s, Churches etc.) provide services and welfare programmes to families with children. “Welfare” is used as a broad concept that includes children’s material resources as well as services targeted to children and families with children. Welfare is also conveyed by the ways in which children and youth are perceived in society, such as how they are involved in decision-making. The study focuses on eight institutions or areas of welfare, namely: - Early childhood education and care (ECEC) - Welfare services at school - Health care of children and youth - Parenting support - Decision-making - Maternity/paternity leave and leave to care for children - Universal child benefits - Income related child benefits. The institutional review was mainly based on a questionnaire that was sent to national informants in May 2007, i.e. contact persons in Ämbetsmannakomittén (the Nordic network of civil servants in the field of social and health policy). A review of policies promoting the welfare of children and youth in the Nordic countries exposes a large variety of services and benefits targeted for them. It is not possible to compare the policies in detail or to draw any far-reaching conclusion in this respect. The general picture is that all the countries belong to the same family. There are clearly more similarities than dissimilarities among ...